Last Train West: Revisiting Romania’s Accession to the EU - Richter, Jochen M. (Tectum Verlag, 2022)
Fifteen years after Romania's controversial accession to the EU, a number of personalities who experienced the events at first hand take stock. Their generally sober analysis has recently become very topical due to Putin's war in Ukraine and the rekindled dispute over the meaning of "spheres of influence" in the 21st century. Discussing the respective roles of NATO and the EU, this book contains important messages about the difficult (and potentially game-changing) trade-off between quick, decisive action and the need for thorough preparation. Romania caught ‘the last train’; perhaps a new direction of travel is needed.